2021
DOI: 10.1155/2021/9950663
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroline-5-Carboxylate Reductase-2 Promotes Colorectal Cancer Progression via Activating PI3K/AKT/mTOR Pathway

Abstract: Aim. The aim of this study was to investigate the effect and underlying pathway of pyrroline-5-carboxylate reductase-2 (PYCR2) on colorectal cancer (CRC). Methods. The Cancer Genome Atlas (TCGA) database was used to analyze PYCR2 expression levels and clinical information. Cell proliferation was evaluated using colony forming and EdU assay. Cell apoptosis rate was determined using flow cytometry. Cell migration and invasion were measured by performing a Transwell assay, and PYCR2, MMP-2, MMP-9, Bax, cleaved ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
11
14
0
Order By: Relevance
“…Our results were in line with those of Yin et al, 13 who were the first to investigate the genetic roles of PYCR2 in CRC oncogenesis, progression and shortened OS. Additionally, our results are similar to those of Wang et al, 7 who assessed the genetic and tissue protein expression of PYCR2 in CRC and other tumor types, and found that levels of PYCR2 are upregulated in CRC tumor tissues at the mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results were in line with those of Yin et al, 13 who were the first to investigate the genetic roles of PYCR2 in CRC oncogenesis, progression and shortened OS. Additionally, our results are similar to those of Wang et al, 7 who assessed the genetic and tissue protein expression of PYCR2 in CRC and other tumor types, and found that levels of PYCR2 are upregulated in CRC tumor tissues at the mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 92%
“…Another role of PYCR2 has been studied in CRC metastases, by the activation of matrix metalloproteinases (MMPs), which mediate CRC cell invasion and migration through degradation of the extracellular matrix (ECM). 13,23 All of the aforementioned results and those of current study show that the upregulation of PYCR2 could lead to CRC progression and metastases through several mechanisms that need to be clarified. To clarify role of PYCR2 in CRC, we assessed the levels of another biomarker, ZBTB18, in sections from CRC and adjacent non-neoplastic tissues of the colonic mucosa.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations